Paroxysmal Autonomic Instability with Dystonia after Pneumococcal Meningoencephalitis - Layal Safadieh; Rana Sharara-Chami; Omar Dabbagh (Case Reports in Medicine)
Streptococcus pneumoniae is a common cause of bacterial meningitis, frequently resulting in severe neurological impairment. A seven-month-old child presenting with Streptococcus pneumoniae meningoencephalitis developed right basal ganglia and hypothalamic infarctions. Daily episodes of agitation, hypertension, tachycardia, diaphoresis, hyperthermia, and decerebrate posturing were observed. The diagnosis of paroxysmal autonomic instability with dystonia was established. The patient responded to clonidine, baclofen, and benzodiazepines. Although this entity has been reported in association with traumatic brain injury, and as a sequel to some nervous system infections, this is the first case, to our knowledge, associated with pneumococcal meningoencephalitis.